Harmful Effects of Synthetic Surface-Active Detergents against Atopic Dermatitis - Hajime Deguchi; Riho Aoyama; Hideaki Takahashi; Yoshinari Isobe; Yutaka Tsutsumi (Hindawi Limited, 2015)
We report herein two cases of intractable atopic dermatitis successfully treated by simply avoiding the contact with surface-active detergents in the daily life and living. The detergents were closely related to the exacerbation and remission of the disease. Steroid ointment was no longer used. We discuss that the removal of horny layer lipids by surface-active detergents accelerates the transepidermal water loss and disturbs the barrier function of the epidermis and thus is intimately involved in the pathogenesis of atopic dermatitis.